The Power of Story: Rhetorical Empathy and Antiracist Organizational Change - Cameron, Brent M (East Carolina University, 2022)
This abstract is more of a note on how to read this thesis because (like this abstract) it is written in an unconventional way. This abstract can also serve as a key for the several recurring acronyms that I use throughout this thesis. In this thesis, I analyze the moments and meeting that resulted in Asao Inoue’s call for a boycott of the Council of Writing Program Administrators (CWPA) in 2021. I argue that personal story and empathy are important rhetorical tools when creating antiracist organizational change—or any organizational change for that matter. In 2020, the CWPA Executive Board (EB) created or invited, a Diversity, Equity, and Inclusion (DEI) Task Force (TF) to help them revise the Outcomes Statement for First Year Composition (OSFYC) with the goal of making it more antiracist. However, during the process, the CWPA EB and the DEI TF experienced a breakdown of communication that resulted in Asao Inoue publishing a blog post accusing the CWPA of unintentionally participating in a white supremacy culture and calling for a boycott of the organization. While Inoue’s call for a boycott of the CWPA was a polarizing, emotional, and otherwise traumatic event for many people in the field of composition and rhetoric, at the time it occurred, I had not heard of the CPWA, knew very little about what a Writing Program Administrator (WPA) does, and knew just as much/little about DEI and antiracist scholarship. To be honest, I mostly learned about all these things while interviewing the people on the CWPA EB and the TF. It is for these reasons that I wrote this thesis in the way that illustrates how I came into it. In this thesis, I tell the story of how I came into this research, the story of the cultural, political, social, and organizational contexts that led up to the CWPA wanting to revise the OSFYC to make it more antiracist, and the story(s) of what led up to Inoue’s call for a boycott of the CWPA. Throughout, I argue that personal story and empathy are important rhetorical tools when creating antiracist organizational change—or any organizational change for that matter. Below is a brief outline and explanation of each chapter. Chapter 1. THE CALL TO ADVENTURE. The first section of this chapter is titled “Crossing the Threshold.” In this section I tell the story of my positionality, how I first began learning about antiracism and antiracist scholarship, and how I came into this research. This personal background information is important because it serves as an admission of my imperfect and ever-growing understanding of the topics, people, and organizations at hand. It is also important because each interview that I conducted began with me telling the interviewees my positionality and how I came into this research. I wanted the interviewees to understand that I was not well versed in DEI or antiracist scholarship and that I was sincerely trying to learn more about it, as well as how they felt about and/or experienced what occurred. The second section of this chapter is titled “The Power of Story.” This section is the literature review. It is divided up into three subsections titled, “Antiracism,” Empathy,” and “Organizational Change.” In each section I emphasize/synthesize the central importance that personal story plays in antiracism, empathy, and organizational change. My intent in this chapter is to illustrate how personal story can serve as a gateway to antiracism by allowing people to cultivate empathy for the lived experiences of marginalized people, which can in turn help foster the kinds of deep understanding and mindfulness needed to create lasting, antiracist organizational change. Chapter 2. THE SEPARATION. The first section of this chapter is titled, “The Road of Trials.” In this section I write about the cultural, political, social, and organizational contexts that surrounded the OSFYC revisions and the meeting that resulted in Inoue’s call for a boycott of the CWPA. These contexts are relevant not only because they serve as the setting of the story(s), but because they played integral roles in the CWPA wanting to move quickly to revise the OSFYC. Each person I interviewed—both on the EB and TF—emphasized how important it is to keep in mind how the feelings of uncertainty and isolation created by things like Covid-19, the racial tensions the nation was experiencing under the Trump presidency, and the viral video of George Floyd’s murder and resulting BLM protests, significantly added to the exigency for revising the OSFYC to make it more antiracist. The second section of this chapter is titled “Methods/Methodology.” In this section I introduce the composite story that I created from all the interviews that I conducted. I also explain who I interviewed, what the interview processes entailed, and how I went about creating my composite story from all the interviewees stories. The third section of this chapter is titled “The Composite of the Story.” This composite story is created from all the stories of the people I interviewed on the EB and TF. It explains what motivated the CWPA to revise the OSFYC to make it more antiracist, how the DEI TF came together, and what the TF’s expectations were regarding the 2020 revisions to the OSFYC. The fourth section of this chapter is titled “The Apotheosis: The meeting.” The section tells the story of what happened at the meeting that resulted in Inoue’s call for a boycott of the CWPA, how people on the EB and TF experienced or felt the meeting, and how the two groups interpreted or felt about each other’s reactions to the TF’s revisions to the OSFYC. Chapter 3. THE BELLY OF THE WHALE. The first section of this chapter is titled “Recrossing the Return Threshold.” In this section I analyze the EB and the TF personal and organizational stories with rhetorical empathy to illustrate how they were all trying to do the most for DEI, but each had separate aims for what they were trying to achieve. Ultimately, I argue that because the EB and TF did not create a story of change together, the CWPA EB’s local goal of empowering and helping WPAs with administrative work, and the TF’s universal goal of questioning and challenging all white language supremacy met with a conflict of interest. The second section of this chapter is titled “Conflicting Games: Finite Outcomes vs. Infinite Goals.” In this section I analyze the EB and TF’s local and universal goals with game theory. I argue that by giving the TF free rein over the revisions in the beginning of the process, the EB consented to the infinite rules of the TF’s universal goal (questioning and challenging all white language supremacy). However, after the EB saw the revisions and realized how they conflicted with the CWPA’s local goals (helping WPA with administrative work) they attempted to apply finite rules to an infinite “goal” that had already been set in motion. This created an impasse, which game theory suggests can occur when finite games and infinite games collide. Chapter 4. “THE RETURN” This chapter is the conclusion. The first section of this chapter is titled “Returning with the Boon.” In this section I reflect on what I learned from listening to and analyzing the TF and EB personal and organizational stories regarding the events that led up to Inoue calling for a boycott of the CWPA and offer some suggestions for going forward. The second section of this chapter is titled “The Call for More Adventures.” In this section I acknowledge the limitations of my research and offer potential areas of further research that could broaden mine.
Keywords: Rhetorical Empathy; Antiracism; Organizational change